An Approach to Design and Implement RFID Middleware System over Cloud Computing - Wenhong Tian; Ruini Xue; Xu Dong; Haoyan Wang (International Journal of Distributed Sensor Networks)
With the development of Internet of things, the number of radio frequency identification (RFID) network readers and tags increases very fast. Large-scale application of RFID networks requires that RFID middleware system can process a large amount of data efficiently, with load-balancing, efficient redundant data elimination, and Web service capabilities so that required information can be transmitted to applications with low overhead and transparency. In view of these objectives and taking especially advantages of virtualization and transparency of Cloud computing, this paper introduces an advanced RFID middleware management system (ARMMS) over Cloud computing, which provides equipment management, RFID tag information management, application level event (ALE) management, and Web service APIs and related functions. ARMMS has different focuses than existing RFID middleware in distributed design, data filtering, integrated load balance, and Web service APIs and designs all these over Cloud. The distributed architecture can support large-scale applications, integrated load-balancing strategy guarantees stability and high performance of the system, and layered and parallel redundancy data elimination scheme makes sure that needed information is transmitted to application level with low overhead; Web service APIs support cross-platform information processing with transparency to lower level RFID hardware.